PENERAPAN ITIKAD BAIK PARA PIHAK PADA PENYELESAIAN SENGKETA TANAH DI DESA SEGARA MAKMUR - Sri Wahyuni; Gisca Pandu Ramanda (Bajang Institute, 2023)
There are several land problems in Segara Makmur Village, this is due to the bad faith of one of the parties in the land sale and purchase agreement. Good faith according to Sutan Remy is the intention of one of the parties in carrying out an agreement not to harm the other party. But what if the land sale and purchase agreement is carried out without good faith from both parties, it will cause harm to the other party. if this happens, it is necessary to settle land disputes in Segara Makmur Village which can be resolved either through litigation or non-litigation. However, in reality, if the settlement through non-litigation is not successful and proceeds to the litigation route, it is necessary to consider several things, such as costs, time, energy, thoughts consumed and focus on resolving the dispute through litigation or court, but not a few feel disadvantaged when unable to prove or lack of evidence. The method used is legal counseling and discussions with residents of Segara Makmur Village regarding the factors that cause disputes and dispute resolution according to Indonesian positive law. The results of the question-and-answer discussion from legal counseling activities obtained 1) that the factors that cause land disputes often arise, including there are intermediaries selling land who are only concerned with profit without paying attention to the land documents that are the object of sale and purchase, not checking the status of land ownership at BPN , the implementation of the sale and purchase agreement is not based on the good faith of the parties including the intermediary 2) How is the application of the principle of good faith in resolving land disputes in Segara Makmur Village